Emerging arboviruses: Why today? - Ernest Gould; John Pettersson; Stephen Higgs; Remi Charrel; Xavier de Lamballerie (One Health, 2017)
The recent global (re)emergence of arthropod-borne viruses (arboviruses), such as chikungunya and Zika virus, was widely reported in the media as though it was a new phenomenon. This is not the case. Arboviruses and other human microbial pathogens have been (re)emerging for centuries. The major difference today is that arbovirus emergence and dispersion are more rapid and geographically extensive, largely due to intensive growth of global transportation systems, arthropod adaptation to increasing urbanisation, our failure to contain mosquito population density increases and land perturbation. Here we select examples of (re)emerging pathogenic arboviruses and explain the reasons for their emergence and different patterns of dispersal, focusing particularly on the mosquito vectors which are important determinants of arbovirus emergence. We also attempt to identify arboviruses likely to (re)emerge in the future.